As práticas da terapia ocupacional: uma investigação a partir do conceito de ocupação coletiva - Allegretti, Maitê Menegazzo (2020)
In the last decades, occupational therapists and occupational scientists have shown the need to discuss / investigate occupational phenomena beyond their individual aspects, considering variables not fully explored so far. Therefore, it is worth investigating the influence and contours of the collective experience in overcoming social inequities. Thus, this research aims to understand how collective practices have been discussed and thought about in occupational therapy, in Brazil, through a dialogue with the concept of collective occupation. This also means identifying possible tensions between individual and collective approaches, with the intention of contributing to overcoming this dichotomy. The thesis aims to: 1. investigate how occupational therapists think / develop the collective dimension of their actions; 2. Identify ideas, theories and interfaces of actions based on the practices of occupational therapists aimed at collectives; 3. identify and describe which models, theories or disciplines, inside and outside occupational therapy, inform the conceptions of these actions; and, 4. from the collaborative work with participants, map the collective practices carried out by them. This is a qualitative and participative study carried out through interviews and collaborative construction of narratives. The data generation was built by the narratives of nine occupational therapists who have been working with collective practices for at least one year. Thematic analysis was used to read the data, as it offers the possibility of searching for the meanings of each participant’ experiences on a personal and collective level. The results were organized in three parts: the trajectories with collective practices; the place where the stories were told from and the understanding of collective practices. Thematic analysis resulted in three major themes addressed in the narratives: 1 - From the individual to the collective: the political and socio-cultural arena of collective practices, 2 - The daily struggles for inclusive practices and 3 - The trajectories for the knowledge necessary to the production of collective practices. The analysis described in this study afforded instigating ways to reflect on the peculiarities found in collective (but also individual) practices developed by occupational therapists, as well as suggested ways to overcome the multiple dichotomies contained therein. This is because, in fact, I consider that both individual and collective practices are fundamental to the practice, although a critical and systematic position on these tensions is still incipient in the intellectual production of Brazilian professionals. In view of the experiences of this group of occupational therapists, I maintain that collective occupation can be a theoretical reference that supports the practices of occupational therapists in confluence with other knowledges, thus strengthening the debate about occupation within occupational therapy and occupational science. I hope to contribute to the political strengthening of the profession, based on the conceptual frameworks of collective occupation.